Voices of linguistic participation in language maintenance and revitalisation: Case of the Nama Dialect of Khoekhoegowab (JULACE: Journal of the University of Namibia Language Centre, 2021)
Although Khoekhoegowab is one of the national languages according to the Namibian constitution, it is not visibly used in many of the formal functions of public domains where we expect to find it as a national language. The data for this study were collected in a town called Keetmanshoop in Namibia. The data collection instrument employed for this study was a semi-structured interview as this allow for the gathering of vast quantities and also due to its greater flexibility. This paper puts agentive speakers at the centre of changes in their communicative economies. This thus suggests the need for an approach that looks at how speakers construct and reconstruct their ideas of language. A notion of linguistic citizenship is attuned to the implications of such communities.
Keywords: language maintenance, language revitalisation, linguistic citizenship, speaker agency, endangered language, Khoesan languages